On The English Translation of the Chinese National Community Consciousness and the Folktales of the Daur Ethnic Group - Zhang, Suojun (Pacific International Journal, 2024)
The Daur’s folktales contain rich national cultural signs, which are the concentrated embodiment of the experience and wisdom from the ancestors of the Daur. They are multi-dimensional, including national language, culture and thought, and are one of the important methods for scholars to study the historical development, ideological inheritance and cultural heritage of the Daur. Taking the consciousness of Chinese National Community as its theoretical guidance and utilizing Daur folktales as a foundational source, this thesis aims to conduct research on English translation methods in terms of semantics and pragmatics. The objective is to further explore the richness of our national culture and ultimately demonstrate that preserving and advancing our cultural heritage is a crucial step in strengthening the consciousness of Chinese National Community.